Neurotoxicity in snakebite--the limits of our knowledge. - Udaya K Ranawaka; David G Lalloo; H Janaka de Silva (Public Library of Science (PLoS), 2013)
Snakebite is classified by the WHO as a neglected tropical disease. Envenoming is a significant public health problem in tropical and subtropical regions. Neurotoxicity is a key feature of some envenomings, and there are many unanswered questions regarding this manifestation. Acute neuromuscular weakness with respiratory involvement is the most clinically important neurotoxic effect. Data is limited on the many other acute neurotoxic manifestations, and especially delayed neurotoxicity. Symptom evolution and recovery, patterns of weakness, respiratory involvement, and response to antivenom and acetyl cholinesterase inhibitors are variable, and seem to depend on the snake species, type of neurotoxicity, and geographical variations. Recent data have challenged the traditional concepts of neurotoxicity in snake envenoming, and highlight the rich diversity of snake neurotoxins. A uniform system of classification of the pattern of neuromuscular weakness and models for predicting type of toxicity and development of respiratory weakness are still lacking, and would greatly aid clinical decision making and future research. This review attempts to update the reader on the current state of knowledge regarding this important issue.